2018
DOI: 10.3389/fmicb.2018.00568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Microbiome Analysis of a Fusarium Wilt Suppressive Soil and a Fusarium Wilt Conducive Soil From the Châteaurenard Region

Abstract: Disease-suppressive soils are soils in which specific soil-borne plant pathogens cause only limited disease although the pathogen and susceptible host plants are both present. Suppressiveness is in most cases of microbial origin. We conducted a comparative metabarcoding analysis of the taxonomic diversity of fungal and bacterial communities from suppressive and non-suppressive (conducive) soils as regards Fusarium wilts sampled from the Châteaurenard region (France). Bioassays based on Fusarium wilt of flax co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 99 publications
2
74
0
Order By: Relevance
“…For example, Arthrobacter (49.7% and 19.1% reduction in infected bulk and rhizosphere soil, respectively) is known to have pathogen suppression potential for Fusarium wilt. 39 In the endophytic compartments, the relative abundances of Lactococcus, Pseudomonas, Bacillus, Falsibacillus, and Leuconostoc, often considered to be plant-beneficial microbes, [40][41][42][43][44][45][46] showed significant decrease compared to the healthy samples. These decreases suggest that the normal endophytic taxa were either actively excluded by the host immune system or outcompeted by moresuccessful colonizers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Arthrobacter (49.7% and 19.1% reduction in infected bulk and rhizosphere soil, respectively) is known to have pathogen suppression potential for Fusarium wilt. 39 In the endophytic compartments, the relative abundances of Lactococcus, Pseudomonas, Bacillus, Falsibacillus, and Leuconostoc, often considered to be plant-beneficial microbes, [40][41][42][43][44][45][46] showed significant decrease compared to the healthy samples. These decreases suggest that the normal endophytic taxa were either actively excluded by the host immune system or outcompeted by moresuccessful colonizers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, higher abundances of the Phyla Actinobacteria, Proteobacteria, Acidobacteria, Gemmatimonadetes, and Nitrospirae were found in soil with specific suppressiveness to Fusarium wilt of strawberry (Cha et al, 2016). More recently, it was shown that fungal and bacterial diversity differed significantly between a suppressive and a conducive soil of Fusarium wilt whereas several of the fungal and bacterial genera known for their activity against F. oxysporum were detected exclusively or more abundantly in the Fusarium wilt-suppressive soil (Siegel-Hertz et al, 2018). Interestingly, studies analyzing the rhizobacterial community composition in soils suppressive or conducive to R. solani revealed that relative abundance of specific bacterial taxa is a more important indicator of suppressiveness than the exclusive presence or absence of specific bacterial families (Mendes et al, 2011;Chapelle et al, 2016).…”
Section: Building Up Of Disease Suppressivenessmentioning
confidence: 99%
“…Soil disease suppressiveness primarily relies on the mechanisms of nutrient competition and specific antagonism caused by soil micro flora [8]. This disease-control capability can be abolished by soil sterilization, and is transferred into the disease-conducive soil by mixing the disease-suppressive soil, indicating that the microbial community confers the property of the soil to prevent the build-up of pathogens and its invasion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, disease suppression is an inherent property of soils that exhibits the compatibility with crop rotation, while the extent of disease suppression is mediated by crop rotation, involving changes of soil microbial activity [14]. Natural suppression is well documented for some fungal diseases, such as Fusarium wilt disease and black root rot caused by T. basicola [8,12]. In other cases, crop monoculture induces soil disease suppressiveness, as evidenced by a decline of disease incidence, following earlier disease outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation